2021
DOI: 10.3390/ijerph182111718
|View full text |Cite
|
Sign up to set email alerts
|

Public Stigma of COVID-19 and Its Correlates in the General Population of China

Abstract: This study aimed to examine the profile of COVID-19-related public stigma and its correlates in the general population of China. A cross-sectional online survey was conducted in China from 7 May to 25 May in 2020. A total of 1212 participants from the general population completed the survey measuring their stigmatizing attitudes towards COVID-19, as well as knowledge and causal attributions of COVID-19. Univariate and multivariate analyses were performed to examine the correlates of COVID-19-related public sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 46 publications
2
45
3
Order By: Relevance
“…Third, the public stigma of the ICC was stronger for participants in their 60s than for participants in their 20s. The results are consistent with the results of a past study [ 54 ]. Stigmatization evoked by public stigma occurs more strongly among people holding collectivistic values than among people holding individualistic values [ 74 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Third, the public stigma of the ICC was stronger for participants in their 60s than for participants in their 20s. The results are consistent with the results of a past study [ 54 ]. Stigmatization evoked by public stigma occurs more strongly among people holding collectivistic values than among people holding individualistic values [ 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, older adult IUCC may hold stronger public stigma associated with COVID-19 than younger adult IUCC [ 54 ]. This is because the cultural orientation of older adult IUCC is more collectivistic than the cultural orientation of younger adult IUCC [ 55 ].…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…Few studies have addressed COVID-19-related public stigma in the general population owing to the lack of a validated tool. These studies have shown that COVID-19-related public stigma is a common phenomenon in several countries [ 15 , 16 , 17 , 18 , 19 , 20 ]. Similar to our study, the prevalence of moderate and high degrees of COVID-19-related public stigma accounts for more than half of the surveyed population in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison group wasn't representative of the general population either, especially regarding the sex ratio (77% women). Female preponderance happens to be common in online surveys where participation is based on a voluntary commitment; recent online surveys regarding COVID-19 (Sulistyawati et al, 2021;Zhang et al, 2021) as well as surveys conducted within the ASD population (Scattoni et al, 2021) have reported similar imbalance towards women. Second, due to the time-sensitive aspect of the research and lockdown circumstances, all data were self-reported.…”
Section: Limitationsmentioning
confidence: 99%